2016
DOI: 10.11118/actaun201664010235
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Insolvency Proceedings: A Case of Visegrad Four

Abstract: Insolvency proceeding and liquidation of bankrupt companies are important topics in days of economic slowdown which aff ected all economies a er fi nancial crisis. This paper aims to fi nd main diff erences between insolvency proceedings in the countries of Visegrad four. The main goal is to describe insolvency law in member countries and then to compare it from the poin of view of main actors. This comparison can help to fi nd which changes and ideas could be applied to improve and make more eff ective the Cz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
(4 reference statements)
2
2
0
Order By: Relevance
“…Even in the case of insolvency law, it is a common approach that however offers a number of opportunities to commit crime. The situation is similar in other Visegrad countries as well (Crhová, Fišerová, Paseková, 2016).…”
Section: Resultssupporting
confidence: 75%
“…Even in the case of insolvency law, it is a common approach that however offers a number of opportunities to commit crime. The situation is similar in other Visegrad countries as well (Crhová, Fišerová, Paseková, 2016).…”
Section: Resultssupporting
confidence: 75%
“…Similar to the present study, a study conducted by Crhova et al (2016) revealed that the state of bankruptcy is declared when it is impossible to meet the obligations towards the creditors. This results in filtration of all of the property and bank accounts to pay as much as possible of these commitments (Crhova et al, 2016). It imposes burden on society resulting in negative effects on the national economy.…”
Section: Discussionsupporting
confidence: 77%
“…(4) Creditor satisfaction. Creditor satisfaction is measured using a negative balance sheet ratio with reference to existing study [56].…”
Section: Moderating Variablesmentioning
confidence: 99%